EFISIENSI PEMANFAATAN FASILITAS DI TANGKAHAN PERIKANAN KOTA SIBOLGA - Zain, Jonny; Syaifuddin, Syaifuddin; Aditya, Yudi (Jurnal Perikanan dan Kelautan, 2011)
This study was conducted at fishing ports in Sibolga city by surveymethods. Survey was conducted on three fishing ports as sample. Its expectedrepresentative all the fishing port at Sibolga city, which divided three catagorize,i.e. large, medium and small fishing port. Purpose of this study is to knowefficiency level of the fishing port’s facilities. The survey result showed averageof effeciency of facilities utilization at Sibolga city fishing port was 50-100%. Theefficiency of heigbour loading was 63.89%, heigbour uploading was 60.70%,manuver area was 70%, depth water of manuver area was 100%, jetty was 50%and ice storage 71.10%.